Successional Pattern and Plant Species Diversity in the Aquatic and Wetland Habitats of North-Central Uttar Pradesh, India - Misra, V. K. (Indian Forester, 2015)
The study area is a portion of upper Gangetic plain. The species composition of the aquatic and wetland vegetation of study area was studied and quantitative indices such as Importance Value Index (IVI), Shannon's diversity index and species richness were computed. A total of 151 species of macrophytes belonging to 91 genera and 45 families have been documented from study sites. These macrophytes were classified into six ecological groups. viz. free-floating hydrophytes (FFH), floating attached hydrophytes (FAH), suspended hydrophytes (SH), submerged attached hydrophytes (SAH), emergent amphibious hydrophytes (EAH) and wetland hydrophytes (WLH). The number of species was highest during rainy season (126 species) followed by winter season (80 species) and least during summers (33 species).